WHISPERING GALLERY MODE LASERS IN ERBIUM/YTTERBIUM CODOPED PHOSPHATE GLASSES - Tran Thi Tam; Dang Quoc Trung; Le Huu Minh; Tran Anh Vu; Do Ngoc Chung; Patrice Feron (ASEAN Journal on Science and Technology for Development, 2007)
The study of whispering gallery mode laser in Er3+/Yb3+ co-doped phosphate glass microsphere has been reported. The coupling was carried out by fiber half taper technique. The microsphere lasers have been studied under pumping at 980 nm, to take full advantage of energy transfer effect from ion Ytterbium to ion Erbium. The observed lasing range extends from 1533 nm to 1612 nm.